Reduction of cardiac and coronary artery doses in irradiation of left-sided breast cancer during inspiration breath hold: A planning study Reduktion von kardialer und koronararterieller Dosisbelastung bei der Bestrahlung von linksseitigem Brustkrebs in Inspiration: Eine Planungsstudie - Schönecker, S.; Heinz, C.; Söhn, M.; Haimerl, W.; Corradini, S.; Pazos, M.; Belka, C.; Scheithauer, H. (Strahlentherapie und Onkologie, 2016)
Background and purpose: The radiation dose received by the heart during adjuvant left-sided breast irradiation plays a crucial role in development of late toxicity. Although the absolute risk of cardiotoxicity can be reduced with modern irradiation techniques, cardiotoxic chemotherapy increases the risk of late damage. Thus, the radiation dose to the heart should be minimized. This study evaluated the influence of different amplitudes of inspiration breath hold (IBH) during simulated left-sided breast irradiation on cardiac doses compared to free breathing (FB). Patients and methods: CT data of 11 lung cancer patients were retrospectively used as left-sided pseudo-breast cancer cases. Two CT scans were used, one during IBH and one during FB, and two treatment plans were generated. Relevant heart, lung, and left anterior descending artery (LAD) parameters were derived from dose–volume histograms. The normal tissue complication probabilities (NTCPs) for the heart were calculated based on the relative seriality model. Inspiration depth was quantified using chest volume and diameter, and correlated thereafter to a possible sparing of heart tissue. Results: Mean reduction of heart dose for IBH compared to FB was 40 % (1.65 vs. 0.99 Gy; p = 0.007). Maximum dose to the heart and LAD could be decreased by 33 % (p = 0.011) and 43 % (p = 0.024), respectively. The mean anteroposterior shift was 5 mm (range 0.9–9.5 mm). Significant negative correlations between the relative change in LAD mean dose and the mean thoracic diameter and volume change, as well as with the absolute change in thoracic diameter were seen. The NTCP for cardiac mortality could be decreased by about 78 % (p = 0.017). Conclusion: For left-sided breast cancer patients, cardiac doses can be significantly decreased with tangential irradiation and IBH.
CRIS-Team Scopus Importer:2025-10-13
Keywords: Breast-conserving surgery; Cardiotoxicity; NTCP; Organs at risk; Radiotherapy